The sustainability edge : how to drive top-line growth with triple-bottom-line thinking - Apte, Suhas, 1952-; Sheth, Jagdish N (Toronto ; Buffalo ; London : University of Toronto Press, 2016)
"Business leaders need to embrace sustainability in order to ensure the lasting success of their organizations. Co-authors Suhas Apte and Jagdish Sheth bring their expertise from practice and from academic to illustrate how business leaders can embed sustainability in a truly holistic and transformative way. Through an examination of such companies as Walmart, AT & T, IKEA and the Tata Group, Apte and Sheth have developed a proven and actionable framework rooted in the real world success of these companies. The case studies reveal how business leaders proactively engage, energize and promote market sustainability to all of their stakeholders including customers, employees, suppliers, investors and the government. The Sustainability Edge enables companies to critically engage their stakeholders and influence them to accept sustainability as part of their core mission."--
Introduction -- Motivating Consumers -- Collaborating with Customers -- Inspiring Employees -- Nurturing Suppliers -- Investing In Communities -- Attracting Investors -- Leveraging Media -- Engaging Government -- Partnering with NGOs -- Stakeholder Sustainability Audit (SSA) Tool.
Includes bibliographical references and index.
Keywords: International business enterprises -- Management -- Environmental aspects -- Case studies; Industrial management -- Environmental aspects -- Case studies; Social responsibility of business -- Case studies; Industrial management -- Environmental aspects; International business enterprises -- Management -- Environmental aspects; Social responsibility of business; Case studies